2022
DOI: 10.1002/mnfr.202200313
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Wheat Peptides Improves Functional Constipation: A Translational Study in Humans and Mice

Abstract: Scope: Wheat peptides (WP) are rich in glutamic acid, glutamine, and other bioactive compounds that may benefit gut function and health. This study aims to evaluate the effects of regular consumption of WP on constipation-induced complications and gut microbiota in humans and mice. Methods and results: A randomized trial of 49 functional constipation participants is conducted. The weekly amount of spontaneous bowel movements (SBM) increases by 2.09 per week after WP treatment, and by 0.40 per week among the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Wheat, corn, and rice, known as the three major cereals of the world, are the staple foods for the vast majority of the world population and are produced in great abundance. It was found that wheat peptides have a high percentage of glutamic acid and glutamine in their amino acid composition, which may ameliorate constipation by improving water-electrolyte metabolism and promoting intestinal motility . Antioxidant peptides, anticancer peptides, and ACE inhibitory peptides were prepared from wheat germ and wheat bran, byproducts of wheat processing.…”
Section: Sourcesmentioning
confidence: 99%
“…Wheat, corn, and rice, known as the three major cereals of the world, are the staple foods for the vast majority of the world population and are produced in great abundance. It was found that wheat peptides have a high percentage of glutamic acid and glutamine in their amino acid composition, which may ameliorate constipation by improving water-electrolyte metabolism and promoting intestinal motility . Antioxidant peptides, anticancer peptides, and ACE inhibitory peptides were prepared from wheat germ and wheat bran, byproducts of wheat processing.…”
Section: Sourcesmentioning
confidence: 99%
“…At present, the exact pathogenesis of STC is not clear, and there is no effective radical cure in the clinic. Previous studies have shown that many factors are involved in the occurrence and development of STC, such as alteration of aquaporin [6][7], structural abnormality of smooth muscle cells [8], disturbance of gastrointestinal hormone secretion [9], and activation of signaling pathways [10].…”
Section: Introductionmentioning
confidence: 99%